Soft-x-ray-induced ionization and fragmentation dynamics of Sc3N@C80 investigated using an ion-ion-coincidence momentum-imaging technique - Xiong, Hui; Obaid, Razib; Fang, Li; Bomme, Cédric; Kling, Nora G.; Ablikim, Utuq; Petrovic, Vladimir; Liekhus-Schmaltz, Chelsea E.; Li, Heng; Bilodeau, Rene C.; Wolf, Thomas; Osipov, Timur; et al. (My University, 2017)
The fragmentation dynamics of an endohedral fullerene, Sc3N@C80, after absorption of a soft-x-ray photon, has been studied with an ion-ion-coincidence momentum-imaging technique. Molecular inner-shell ionization at 406.5 eV, targeting the Sc (2p) shell of the encapsulated Sc3N moiety and the C (1s) shell of the C80 cage, leads to the cage fragmentation through evaporation of C2, emission of small molecular carbon ions (Cn+, n≤24), and release of Sc and Sc-containing ions associated with the carbon cage opening or fragmentation. The predominant charge states of Sc and Sc-containing ionic fragments are +1 despite an effective Sc valence of 2.4, indicating that charge transfer or redistribution plays an important role in the fragmentation of the encaged Sc3N. Sequential emission of two out of the three Sc atoms of the encaged moiety, via Coulomb explosion in the form of Sc+ or Sc-containing ions, is significant. We also find that the resonant excitation of the Sc (2p) shell electrons significantly increased the yield of the parent Sc3N@C80 and its fragment ions, partially attributed to the collision of the energetic Auger electrons from the Sc site with the carbon cage.
Citation: Xiong, H., Obaid, R., Fang, L., Bomme, C., Kling, N. G., Ablikim, U., … Berrah, N. (2017). Soft-x-ray-induced ionization and fragmentation dynamics of ${\mathrm{Sc}}_{3}\mathrm{N}@{\mathrm{C}}_{80}$ investigated using an ion-ion-coincidence momentum-imaging technique. Physical Review A, 96(3), 033408. https://doi.org/10.1103/PhysRevA.96.033408
Keywords: Atomic & molecular clusters; Molecular spectra; Photodissociation; Single- and few-photon ionization & excitation